Mechanics of machines - Shamsudin, Shamsul Anuar; Abd Samad, Md Fahmi; Abdollah, Mohd Fadzli; Abdullah, Mohd Azman (Penerbit UTeM Press, 2023)
This is the first time the Mechanics of Machine course has been published in module form. This module is dedicated to all instructors who have contributed to the notes. The Mechanics of machine course has long been offered at Universiti Teknikal Malaysia Melaka.